Barriers and enablers to deprescribing in people with a life-limiting disease: A systematic review. (January 2019) - Paque, Kristel; Vander Stichele, Robert; Elseviers, Monique; Pardon, Koen; Dilles, Tinne; Deliens, Luc; Christiaens, Thierry
Background: Knowing the barriers/enablers to deprescribing in people with a life-limiting disease is crucial for the development of successful deprescribing interventions. These barriers/enablers have been studied, but the available evidence has not been summarized in a systematic review. Aim: To identify the barriers/enablers to deprescribing of medications in people with a life-limiting disease. Design: Systematic review, registered in PROSPERO (CRD42017073693). Data sources: A systematic search of MEDLINE, Embase, Web of Science and CENTRAL was conducted and extended with a hand search. Peer-reviewed, primary studies reporting on barriers/enablers to deprescribing in the context of explicit life-limiting disease were included in this review. Results: A total of 1026 references were checked. Five studies met the criteria and were included in this review. Three types of barriers/enablers were found: organizational, professional and patient (family)-related barriers/enablers. The most prominent enablers were organizational support (e.g. for standardized medication review), involvement of multidisciplinary teams in medication review and the perception of the importance of coming to a joint decision regarding deprescribing, which highlighted the need for interdisciplinary collaboration and involving the patient and his family in the decision-making process. The most important barriers were shortages in staff and the perceived difficulty or resistance of the nursing home resident's family – or the resident himself. Conclusion and implications of key findings: The scarcity of findings in the literature highlights the importance of filling this gap. Further research should focus on deepening the knowledge on these barriers/enablers in order to develop sustainable multifaceted deprescribing interventions in palliative care.